Dynamic shifts in social network structure and composition within a breeding hybrid population. Issue 1 (6th September 2020) - Zonana, David M.; Gee, Jennifer M.; Breed, Michael D.; Doak, Daniel F.
Abstract: Mating behaviour and the timing of reproduction can inhibit genetic exchange between closely related species; however, these reproductive barriers are challenging to measure within natural populations. Social network analysis provides promising tools for studying the social context of hybridization, and the exchange of genetic variation, more generally. We test how social networks within a hybrid population of California Callipepla californica and Gambel's quail Callipepla gambelii change over discrete periods of a breeding season. We assess patterns of phenotypic and genotypic assortment, and ask whether altered associations between individuals (association rewiring), or changes to the composition of the population (individual turnover) drive network dynamics. We use genetic data to test whether social associations and relatedness between individuals correlate with patterns of parentage within the hybrid population. To achieve these aims, we combine RFID association data, phenotypic data and genomic measures with social network analyses. We adopt methods from the ecological network literature to quantify shifts in network structure and to partition changes into those due to individual turnover and association rewiring. We integrate genomic data into networks as node‐level attributes (ancestry) and edges (relatedness, parentage) to test links between social and parentage networks. We show that rewiring of associations between individuals that persist across network periods, rather than individual turnover, drives the majority of the changes in network structure throughout the breeding season, and that the traits involved in phenotypic/genotypic assortment were highly dynamic over time. Social networks were randomly assorted based on genetic ancestry, suggesting weak behavioural reproductive isolation within this hybrid population. Finally, we show that the strength of associations within the social network, but not levels of genetic relatedness, predicts patterns of parentage. Social networks play an important role in population processes such as the transmission of disease and information, yet there has been less focus on how networks influence the exchange of genetic variation. By integrating analyses of social structure, phenotypic assortment and reproductive outcomes within a hybrid zone, we demonstrate the utility of social networks for analysing links between social context and gene flow within wild populations. Abstract : Social networks play an important role in population processes such as the transmission of disease and information, yet there has been less focus on how networks influence the exchange of genetic variation. By integrating analyses of social structure, phenotypic assortment, and reproductive outcomes within a quail hybrid zone, the authors demonstrate the utility of social networks for analysing links between social context and gene flow within wild populations.